Antifungal Effect of A Chimeric Peptide Hn-Mc against Pathogenic Fungal Strains - Jin-Young Kim; Seong-Cheol Park; Gwangbok Noh; Heabin Kim; Su-Hyang Yoo; Il Ryong Kim; Jung Ro Lee; Mi-Kyeong Jang (Antibiotics, 2020)
It is difficult to identify new antifungal agents because of their eukaryotic nature. However, antimicrobial peptides can well differentiate among cell types owing to their variable amino acid content. This study aimed to investigate the antifungal effect of Hn-Mc, a chimeric peptide comprised of the N-terminus of HPA3NT3 and the C-terminus of melittin. We evaluated its potent antifungal activity at low minimal inhibitory concentrations (MICs) ranging from 1–16 μM against pathogenic yeast and molds. The cell-type specificity of Hn-Mc was mediated through the formation of a random α-helical structure to mimic the fungal membrane environment. Furthermore, Hn-Mc caused cell death in C. tropicalis and F. oxysporum by inducing apoptosis via the generation of reactive oxygen species (ROS) due to mitochondrial damage. The present results indicate that Hn-Mc has a high affinity for the fungal plasma membrane and induces apoptosis in fungal cells, and provide guidance for the development of new antifungal agents.